Kawasaki disease: always straight to the heart?. (24th August 2012) - Clausen, Henning; Howarth, Claire; Giardini, Alessandro
Abstract : Kawasaki disease is an important differential diagnosis when evaluating prolonged fever in childhood. Although the aetiology of this vasculitic disease process remains obscure, prompt recognition and treatment significantly reduces vascular complications such as coronary artery aneurysms. Patients presenting with atypical or incomplete diagnostic features remain a challenge. Here the authors describe the atypical features of Kawasaki disease that led to profound acute hearing loss in a 6-year-old boy with complex congenital heart disease. Coronary changes were not seen on early follow-up, but the patient required bilateral hearing aids. Considering Kawasaki disease early, even in the possibly confusing context of complex congenital heart disease and atypical symptomatology, is crucial to avoid long-term sequelae.